Karakterisasi Air Hasil Filtrasi Instalasi Pengolahan Air Sederhana Berdasarkan Variasi Waktu Filtrasi dan Ketebalan Media Arang Ampas Teh - Aprilianto, Zaka; Oktaviananda, Cyrilla (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
The increase in population and the development of the industrial sector have resulted in water pollution and a decrease in the quality of clean water. Water treatment with filtration method is an effort to reduce the concentration of pollutants in water using adsorbents. This study aims to test the quality of water filtration results using a simple water treatment plant with tea grounds as the adsorbent. The media used in the simple water treatment plant are coconut fiber, zeolite sand, silica sand, tea grounds, gravel, and sponge. The water quality parameters tested were TDS (Total Dissolved Solid) analysis, pH analysis, organoleptic analysis, total hardness analysis, fixed hardness, temporary hardness and COD analysis. The independent variables in this study were the thickness of tea pulp media (0 cm, 3 cm, 5 cm, and 7 cm) and filtration time (20 minutes, 40 minutes, and 60 minutes). The results showed that the combination of tea pulp media height and process time had no significant effect on TDS, pH, hardness, COD, and organoleptic values. The optimum condition of tea pulp media height and process time with filtration-adsorption process for pH characteristics is in the treatment of 0 cm charcoal height, on the characteristics of total hardness and fixed hardness is in the treatment of 0 cm charcoal height and 20 minutes process time, while the optimum condition of temporary hardness is in the treatment of 7 cm charcoal height and 20 minutes process time.